Rehabilitation and palliation of cancer patients (Patient care) - Delbrück, Herrmann. (Collection de L'Académie Européenne de Médecine de Réadaptation,, 2007)
To improve quality of life for cancer patients has been the endeavour of the author for the past 25 years in rehabilitation and palliation. To maintain quality of life is an important challenge not only for health aftercare service, but also in palliative and terminal situations. The invasiveness of some of the current therapies and the restricted life expectancy of many patients led to the change in therapeutic paradigms. Rehabilitation and palliation have become an essential part of modern comprehensive cancer care. There are many excellent text books in cancer management which provide therapeutic recommendations thereby influencing the disease. Quality of life is now the second parameter after survival used to evaluate the effectiveness of first line oncologial therapies and is still the first parameter of most therapies in the case of recurrence. It contains experiences of the author and specific instructions how to assess, treat and evaluate rehabilitative and palliative measures.